2009
DOI: 10.1139/w08-102
|View full text |Cite
|
Sign up to set email alerts
|

Improved cure of bacterial vaginosis with single dose of tinidazole (2 g),Lactobacillus rhamnosusGR-1, andLactobacillus reuteriRC-14: a randomized, double-blind, placebo-controlled trial

Abstract: Bacterial vaginosis (BV) is the most prevalent vaginal infection worldwide and is characterized by depletion of the indigenous lactobacilli. Antimicrobial therapy is often ineffective. We hypothesized that probiotic Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 might provide an adjunct to antimicrobial treatment and improve cure rates. Sixty-four Brazilian women diagnosed with BV were randomly assigned to receive a single dose of tinidazole (2 g) supplemented with either 2 placebo capsules or 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 33 publications
5
88
0
3
Order By: Relevance
“…However, previous studies found that vaginal lactobacilli can be restored to some extent in postmenopausal women who receive hormone replacement therapy (Heinemann & Reid, 2005). The normal microbiota of the vagina may prevent the colonization of pathogenic micro-organisms, including those responsible for bacterial vaginosis (BV) (Anukam et al, 2006;Martinez et al, 2009), yeast infections (Martinez et al, 2009), urinary tract infections (Cadieux et al, 2009;Shiraishi et al, 2011) and sexually transmitted diseases (Bolton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies found that vaginal lactobacilli can be restored to some extent in postmenopausal women who receive hormone replacement therapy (Heinemann & Reid, 2005). The normal microbiota of the vagina may prevent the colonization of pathogenic micro-organisms, including those responsible for bacterial vaginosis (BV) (Anukam et al, 2006;Martinez et al, 2009), yeast infections (Martinez et al, 2009), urinary tract infections (Cadieux et al, 2009;Shiraishi et al, 2011) and sexually transmitted diseases (Bolton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The probiotic Lactobacillus rhamnosus GR-1 was selected for use as an intervention in the present study since it has a safe history of use (8,9,21) and was already produced in Mwanza, Tanzania, as part of the Western Heads East network of microenterprise community-run kitchens (22). For the purposes of the present study, the yogurt was further supplemented with dried ground Moringa oleifera (Moringa), a readily available plant, rich in vitamin A, proteins, carbohydrate, fiber, minerals, calcium, magnesium, phosphorus, potassium, copper, iron, zinc, and manganese (23) and used commonly in the management of malnutrition (24).…”
mentioning
confidence: 99%
“…In addition to these concerns, the effects of probiotics have been shown to be strain specific; therefore, the use of an individual micro-organism strain is only justified in procuring the specific benefits that it has been proven to convey (Martinez et al, 2009;Pham et al, 2008, World Health Organisation, 2002. For example, a specific strain of Lactobacilli which has been proven to improve travellers' diarrhoea cannot also be assumed to improve eczema.…”
Section: Probioticsmentioning
confidence: 99%